Pengaruh Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai Pada Kantor Badan Pengelola Keuangan Dan Aset Daerah (BPKAD) Kota Bima - Taufik; Muhamad Badar (Pusat Riset dan Inovasi Nasional, 2023)
this study aims to determine whether there is an influence of Human Resource Development on Employee Performance at the Office of the Regional Financial and Asset Management Agency (BPKAD) Kota Bima. The results of this study indicate that the Human Resource Development variable has a significant effect on Employee Performance at the Regional Financial and Asset Management Agency (BPKAD) Office of Bima City